Performance of Balinese Pigs Fed with Banana Stem and Lamtoro (Leucaena leucocephala) Leaf-Based Diets Fermented for Different Durations in the Sukanadi Women Farmer Group - Yan Tonga; Sutapa, I Gede; Yudiastari, Ni Made; Ama, Desandro T.; Jati, Ignasius Ghari (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Balinese pigs are one of the livestock commodities that the community has raised. However, their maintenance is still carried out traditionally by utilizing makeshift feed ingredients in the vicinity, so the appearance of Balinese pigs is not optimal with indicators, and their growth is still below the NRC standard. With simple maintenance, the weight gain of local pigs can only be achieved 180-260 gr/head/day, which is still below the NRC standard of 500-750 gr/head/day. Therefore, efforts must be made to increase weight gain by improving feed quality through fermentation. This study aims to improve the performance of local Balinese pigs by treating feed with various fermentation times from surrounding materials such as banana stems, forage, and complete feed mixtures (rice bran, fine corn, and concentrates). This study used a complete randomized design with fermented feed treatment with variations in fermentation time, namely feed without fermentation (F0), feed fermented for 14 days (F1), and feed fermented for 28 days (F2). Each treatment used 3 Balinese/local pigs of 2-3 months old weaning age with a weight range of 10-12 kg. The banana stem and lamtoro leaf-based feedstuffs fermented for 28 days showed significant results or the best on the performance of Balinese pigs. Contribution to Sustainable Development Goals (SDGs):SDG 1: No PovertySDG 2: Zero hunger SDG 9: Industry, Innovation, and Infrastructure SDG 12: Responsible Consumption and Production SDG 13: Climate ActionSDG 15: Life on Land